SEKSUALITAS DAN KETAHANAN KELUARGA - Masri Singarimbun (Populasi, 1997)
Sexuality is closely related to thefamily resistance, and the safe sexual behavior is considered as a characteristic of faithfulness. However, it seems that the test of a husband's or a wife's faithfulness becomes heavier since the prostitution location can nearly be found everywhere. Sexual freedom in the youth's circle is a sign that such a location will not easily disappear in the earth, because thefreedom becomes one of the prostitution causes.